A Study on Impact of Artificial Intelligence in Cyber Security - Khamitkar, Nikhil S; Mente, Rajivkumar S; Chendage, Bapu D (International Journal of Computer Sciences and Engineering, 2025)
Cyber security ensures the protection of devices, software, and data that are connected to the internet from potential risks, against attacks, damage, or unauthorized access. As maximum personal information and activities shift online, the significance of cyber security has grown. Various cyber security threats include hacking, malware, phishing, and ransomware. This paper reviews various Conventional methods of cyber security focus on protecting systems and data from digital threats., application of AI in cyber security, future of AI in cyber security, regarding AI in multiple area, intelligent techniques to facilitate security, disadvantages of using AI and machine learning in cyber security.